Solar photospheric spectrum microvariability: I. Theoretical searches for proxies of radial-velocity jittering - Dravins, Dainis; Ludwig, Hans-Günter (Astronomy and astrophysics, 2023)
Context. Extreme precision radial-velocity spectrometers enable extreme precision in stellar spectroscopy. Searches for low-mass exoplanets around solar-type stars are limited by various types of physical variability in stellar spectra, such as the short-term jittering of apparent radial velocities on levels of similar to 2 m s(-1).Aims. To understand the physical origins of radial-velocity jittering, the solar spectrum is assembled, as far as possible, from basic principles. Solar surface convection is modeled with time-dependent 3D hydrodynamics, followed by the computation of high-resolution spectra during numerous instances of the simulation sequence. The behavior of different classes of photospheric spectral lines is monitored throughout the simulations to identify commonalities or differences between different classes of lines: weak or strong, neutral or ionized, high or low excitation, atomic or molecular.Methods. Synthetic spectra were examined. With a wavelength sampling lambda/Delta lambda similar to 1 000 000, the changing shapes and wavelength shifts of unblended and representative Fe I and Fe II lines were followed during the simulation sequences. The radial-velocity jittering over the small simulation area typically amounts to +/- 150 m s(-1), scaling to similar to 2 m s(-1) for the full solar disk. Flickering within the G-band region and in photometric indices of the Str & ouml;mgren uvby system were also measured, and synthetic G-band spectra from magnetic regions are discussed.Results. Most photospheric lines vary in phase, but with different amplitudes among different classes of lines. Amplitudes of radial-velocity excursions are greater for stronger and for ionized lines, decreasing at longer wavelengths. Matching precisely measured radial velocities to such characteristic patterns should enable us to remove a significant component of the stellar noise originating in granulation.Conclusions. The granulation-induced amplitudes in full-disk sunlight amount to similar to 2 m s(-1); the differences between various line groups are an order of magnitude less. To mitigate this jittering, a matched filter must recognize dissimilar lineshifts among classes of diverse spectral lines with a precision of similar to 10 cm s(-1) for each line group. To verify the modeling toward the filter, predictions of center-to-limb dependences of jittering amplitudes for different classes of lines are presented, testable with spatially resolving solar telescopes connected to existing radial-velocity instruments.